The prevalence of depressive symptoms in the prepartum and postpartum period : a study of low-income women in the Western Cape, South Africa - Storkey, Karen (Stellenbosch : University of Stellenbosch, 2006)
Thesis (MA (Psychology))--University of Stellenbosch, 2006.